Simultaneous measurement of refractive index and conductivity based on metamaterial absorber. (23rd October 2017) - Wang, Wei; Yan, Feng-Ping; Tan, Si-yu; Zhang, Lu-na; Bai, Zhuo-Ya; Cheng, Dan; Zhou, Hong; Hou, Ya-Fei
Abstract: An algorithm for the metamaterial sensors to simultaneously measure the refractive index (RI) and conductivity of the analyte is introduced. To verify the algorithm, a square ring metamaterial absorber is numerically calculated as a specific example in the terahertz frequency. Firstly, the sensing performances of the absorber on the RI and conductivity are evaluated separately. Then the relationship expressions between dual variables (frequency shift (FS) and amplitude modulation (AM)) and two arguments (RI and conductivity) can be obtained through mathematical fitting process. By reversely solving this equations set, the conductivity and RI of the analyte can be expressed as another equations set that can be solved easily. The proposed algorithm offers an effective method to determine RI and conductivity of the analyte by measuring the AM and FS of the reflection dip of the absorber sensor. To validate the effectiveness and accuracy of the algorithm, the FS and AM obtained from the simulations are plugged into the reverse equations set. Then the calculated n and σ are compared to their responding original values. The maximum percentage error between them are both less than 0.83%, which are small enough to illustrate the rightness of the proposed method.